Development of interactive multimedia based on lectora inspire in kingdom monera material - Sayyidah Asmah; Laili Fitri Yeni; Titin Titin (JPBIO (Jurnal Pendidikan Biologi), 2020)
Interactive multimedia based on Lectora inspire referred to in this research was learning media of based ICT created to use the Lectora inspire computer program. This research aims to develop learning media and determine students' responses to interactive multimedia based on Lectora inspire that appropriate to be used as learning media in the kingdom monera. This research was the ADDIE development model consisting of five stages of analyzing, design, develop, implement, and evaluate. The students response questionnaire consisted of 3 aspects namely cognitive, affective, and conative consisting was 22 items. Research subjects is students of class XI in SMA Negeri 2 Pontianak, SMA Negeri 10 Pontianak, and MAN 1 Pontianak. The results of interactive multimedia based on Lectora inspire validation for the eligibility to obtain a Content Validity Index value was 1.00 and declared valid. A small-scale trial consisting of 18 students received an average rating is a good category. Whereas a large-scale trial consisting of 36 students obtained an average score in the very good category. The results obtained it was concluded that interactive multimedia based on Lectora inspire was suitable for use as a medium in schools and there needs to be implemented to see acheviement.Keywords: Kingdom monera, lectora inspire, interactive multimedia, response